Functional Outcomes of Open Reduction and Internal Fixation of Comminuted Radial Head Fractures Using Low-Profile Minifragment Plates - Khalid, Saad Ullah; Akram, Rizwan; Fatima, Syeda Tatheer; Saif, Mian Muhammad; Iqbal, Muhammad Fahad; Ali Shah, Syed Qasim (Indus Journal of Bioscience Research, 2025)
Background and Aim: Displaced comminuted radial head fractures may compromise elbow stability and forearm rotation. This study assessed early functional and radiographic outcomes after open reduction and internal fixation using low-profile minifragment plates. Materials and Methods: A prospective observational study was conducted in the Orthopedic Department, Ghurki Trust Teaching Hospital, Lahore, from August 2024 to February 2025. Seventy adults with Mason type III fractures or reconstructable Mason type IV fracture-dislocation underwent fixation using 2.0 to 2.4 mm minifragment plates. Outcomes at 12 weeks included Mayo Elbow Performance Score, range of motion, visual analogue scale pain, radiographic union, complications, and multivariable logistic regression for Mayo Elbow Performance Score below 80. Results: Mean age was 43.8 ± 15.2 years; 42 patients 60.0% were male. Mason type III occurred in 52 patients 74.3% and type IV in 18 patients 25.7%. Coronoid fractures were present in 18 patients 25.7% and ligamentous injuries in 12 patients 17.1%. Mean time to surgery was 4.2 ± 2.8 days and operative time 78.4 ± 22.6 minutes. Mean Mayo Elbow Performance Score was 89.3 ± 8.4 (median 91; range 68–100): excellent 48 68.6%, good 16 22.8%, fair or worse 6 8.6%. Flexion was 134.6 ± 9.2 degrees, extension deficit 6.8 ± 5.4 degrees, pronation 73.2 ± 11.4 degrees, and supination 72.8 ± 10.6 degrees. Mean pain score was 1.8 ± 1.5; pain 2 or less occurred in 56 80.0%, and functionally normal motion in 54 77.1%. Union by 12 weeks occurred in 66 94.3% with mean 8.4 ± 2.1 weeks; delayed union occurred in 4 5.7%. Complications occurred in 12 17.1%, including stiffness 4 5.7%, implant impingement 3 4.3%, fixation failure 2 2.9%, nonunion 1 1.4%, heterotopic ossification 7 10.0%, and reoperation 3 4.3%. Trends for Mayo Elbow Performance Score below 80 were observed with coronoid fracture (odds ratio 3.12; P = 0.129), ligament injury (odds ratio 4.16; P = 0.069), and type IV fractures (odds ratio 2.84; P = 0.149). Conclusion: Early outcomes after low-profile minifragment plating were favorable with high union rates and acceptable short-term morbidity.